SCHOOL LIBRARY MANAGEMENT DEVELOPMENT MODEL FOR LEARNING RESOURCE OPTIMIZATION - Tia Atikah; Aaf Afiah; Anis Zohriah; Apud Apud (LP2M IAI Al-Khairat Pamekasan, 2026)
Effective library management is a key factor in improving the quality of services provided to users. Libraries serve as centers of information and learning resources that play a strategic role in supporting academic activities and enhancing community literacy. Library management can be understood as a process of organizing and optimizing human resources, particularly librarians, to achieve the objectives of the library based on organizational principles and established theories of library science. The purpose of this study is to describe the management of libraries in madrasahs and dayahs, with a specific focus on developing organizational structures that include goal setting, task formulation, activity planning, and defining the roles of librarians. Such structures are intended to make libraries more efficient and effective in their utilization. This research employs a descriptive qualitative method, which allows the researcher to gain a deeper understanding of the phenomenon under study and to investigate library management practices in detail. Through this approach, the study provides a comprehensive picture of how libraries can be optimized as centers of learning, thereby improving service quality, strengthening literacy, and supporting independent learning among students.